Characterization of precipitation and frequency of rainy days in the municipality of Botucatu – São Paulo – Brazil - Franco, Jose Rafael [UNESP]; de Oliveira, Victor Crespo [UNESP]; Pai, Alexandre Dal [UNESP]; Sarnighausen, Valéria Cristina Rodrigues [UNESP]; Rodrigues, Sérgio Augusto [UNESP]; Campos, Firmo Souza [UNESP]; Pai, Enzo Dal [UNESP] (Research Square Platform, 2024)
Knowledge of the rainfall regime is vital information for agricultural and environmental activities. Rainfall is a component of the hydrological cycle, in which liquid water uses energy from the environment to change its phase to the gaseous phase. The cooling of this water vapor causes condensation and subsequent precipitation. Mean precipitation values, distribution during the year, variation between years, and maximum and minimum values are useful parameters for rural and urban planning. This study aimed to characterize the rainfall regime in the municipality of Botucatu through the assessment of precipitation and frequency of rainy days, considering the history of 52 years. The mean local precipitation during the period of analysis was 1,525.53 ± 284.71 mm. The rainiest month is January, with 284.92 ± 123.87 mm, which is also one of the months with the highest variability. August is the month with the lowest rainfall volume, reaching 40.40 ± 43.72 mm. The highest rainfall volume was observed in 1983, with 2,278 mm accumulated and 147 days of rain. In 1984, the lowest rainfall volume was observed, reaching 964 mm, and only 82 days of rain. The mean number of annual rainy days is 107 ± 14 days. In terms of the frequency of rainy days, 50% of the years in the analyzed history had 12 days or more of rainfall in January, February, March, November, and December. The remaining 50% of the years had up to two days of rain in July and up to 4 days in June.